EFFICACY OF ULTRA-LOW VOLUME DISINFECTION WITH HYDROGEN PEROXIDE VAPOUR IN A POULTRY HATCHERY - G. Zhelev; Il. Lazarov (Trakia Journal of Sciences)
Good hygiene in the hatcheries is one of the most important factors for normal hatching, low embryonic mortality and healthy chickens. The best disinfectant in these sites should combine high antimicrobial efficiency, lack of damages on the eggs and embryos, and has to be harmless for the staff and the environment. One of the few disinfectants which meets all these conditions is hydrogen peroxide. This study presents data on the effectiveness of disinfection with hydrogen peroxide vapour in a poultry hatchery. Nocolyse One Shot disinfectant (Oxy Pharm, France), containing 12% hydrogen peroxide and silver ions was used, which was applied by Nocospray (an ultra-low volume application device, Oxy Pharm, France) in a dose of 5 mL per 1 m3 . The results obtained show high efficiency of the disinfection treatments. The achieved microbial reduction in the hatchers was in the range from 95.51% (1.35 log10) for the floor to 99.89% (2.95log10) for the air. The reduction of microbial contamination during the processing of hatching eggs was in the rate of 99.75% (2.6 log10). The high efficiency of the treatments, the low toxicity and ecological safety of the hydrogen peroxide and the ease way of its application are the reasons to extend the implementation of the method in hatchery hygiene practices.